Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Guru di Madrasah Aliyah Negeri Tana Toraja - Sulthan Massora; Olivia Devi Yulian Pompeng; Lisa Kuniasari Wibisono (Universitas Kristen Indonesia Toraja, 2025)
This study aims to analyze the effect of workload and work stress on the performance of teachers at Madrasah Aliyah Negeri Tana Toraja. The study uses a quantitative approach with a population of 38 teachers, all of whom were selected as the sample using the total sampling technique. Data collection was carried out using questionnaires, and data analysis was performed using multiple linear regression assisted by SPSS version 26. The results show that workload has a significant positive effect on teacher performance, with a t-value of 2.081, which is greater than the t-table value of 2.030, indicating a significant positive relationship between the two. In addition, work stress also has a significant positive effect on teacher performance, with a t-value of 8.046, which is greater than the t-table value of 2.030. Simultaneously, both variables have a significant effect on teacher performance at Madrasah Aliyah Negeri Tana Toraja. In conclusion, an increase in workload and work stress, when managed properly, can improve teacher performance. Therefore, it is important for the school to pay attention to managing workload and work stress to optimize teacher performance.